MENINGKATKAN HASIL BELAJAR IPS MENGGUNAKAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER SISWA KELAS IV SDN 2 WAMEO - Matje, Irman (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2022)
The purpose of this study was to determine the improvement of social studies learning outcomes using the Numbered Head Together type of cooperative learning model for fourth grade students of SD Negeri 2 Wameo. The conclusions of the research results: (1) The results of the first cycle research show that using the Numbered Head Together type of cooperative learning model, the average value of student learning outcomes is 66.07 and learning completeness reaches 60.71% or there are 17 students from 28 students who have completed study. These results indicate that in the first cycle classically students have not finished studying, because students who get a score of 65 are only 60.71% smaller than the desired completeness percentage, which is 85 %, and (2) Furthermore, from the results of the second cycle research shows using the cooperative learning model Numbered Head Together type, the average value of student learning outcomes is 73.21 and the percentage of complete learning reaches 85.71% or there are 24 students from 28 students who have finished studying. These results indicate that in the second cycle classically students have finished studying, because students who get a score of 65 are 85.71%, the percentage of completeness desired is 85%